Multiple Cause of Death, 1984 ([Verlag nicht ermittelbar], 1993)
This data collection presents information about the causes of deaths occurring in the United States during 1984. Information is provided concerning original and underlying causes of death, nature of injury, type of illness, place of death, and whether there were multiple conditions that caused the death. In addition, data are provided on date of death, and on sex, race, age, marital status, and origin or descent of the deceased. Also included is information on residence of the deceased (state, county, city, region, and whether the county was a metropolitan or a nonmetropolitan area). Data on whether an autopsy was performed and the site of accidents are also provided.